Molybdenum phosphide as an efficient electrocatalyst for the hydrogen evolution reaction - Xiao, Peng (2014)
Electrochemical production of hydrogen from water has been directed to the search for non-noble metal based and earth-abundant catalysts. In this work, we propose a novel cost-effective catalyst, molybdenum phosphide that exhibits high activity towards the hydrogen evolution reaction (HER) in both acid and alkaline media even in bulk form. Comparative analysis of Mo, Mo3P and MoP as catalysts for HER clearly indicates that phosphorization can potentially modify the properties of the metal and different degrees of phosphorization lead to distinct activities and stabilities. Theoretical calculations by density functional theory also show that a simple phosphorization of molybdenum to form MoP introduces a good ‘H delivery’ system which attains nearly zero binding to H at a certain H coverage. With the combination of experimental results and theoretical calculations, this work has enlightened a new way of exploring cost-effective catalysts for HER.